FEATURES OF FUNCTIONING OF THE SOFTWARE COMPLEX AT THE STAGE OF OPERATION OF ELEMENTS OF STRUCTURES FROM COMPOSITE MATERIALS - Шевченко, О. А. (Proceedings of National Aviation University (archive), 2021)
The concept of solving the problem of optimizing the technology of repair of aircraft components from composite materials that have received operational damage with the help of software is proposed. The methods on which the software package should be based are determined, and the peculiarities of its work at the stage of operation are considered.